Comparison of Effectiveness of High Pressing and Defensive Strategies in Counteracting Opponent Attacks - Andi Saiful Alimsyah (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
The tactical approach in football has evolved significantly over the past decades, with high pressing and defensive strategies representing two fundamental paradigms in match performance. This research aims to compare the effectiveness of high pressing versus defensive strategies in addressing opponent attacks through a comprehensive analysis of tactical implementations. The study employed a quantitative approach analyzing 120 professional football matches from the 2022-2023 season, incorporating tactical metrics including ball recovery rate, defensive success percentage, goal conceding rate, and offensive transition effectiveness. Data were collected from video analysis and official match statistics, with statistical comparisons conducted using independent t-tests and correlation analyses. Results demonstrated that high pressing strategies achieved an average ball recovery rate of 68.4% in the opponent's half, with 58.2% defensive success rate, although they exhibited a higher defensive vulnerability at an average of 1.8 goals conceded per match. Conversely, defensive strategies recorded a lower ball recovery rate of 42.1% but achieved superior defensive stability with 1.2 goals conceded per match and 75.6% defensive success rate. However, defensive approaches demonstrated reduced offensive transition opportunities (3.4 per match versus 7.6 for high pressing). The findings suggest that high pressing strategies facilitate greater attacking opportunities and ball possession control but require exceptional defensive organization to minimize counter-attack risks. Defensive strategies provide tactical stability and defensive security but potentially limit offensive opportunities. The effectiveness of either strategy appears context-dependent, influenced by squad composition, opponent characteristics, and match situational factors. This research contributes to understanding how tactical strategic choices impact match outcomes and provides evidence-based recommendations for tactical implementation based on specific competitive contexts.